The macro economy today - Schiller, Bradley R. (McGraw-Hill, 2000)
The Macro Economy today is well-known for its balanced presentation and for unique chapters. In addiction, the AS/AD model is now separated from the Keynesian Cross, which gives instructors the freedom to cover the topics they want to include and easily exclude the ones they don't. This isn't a highly opinionated text. It doesn't assert that only long-run issues matter or that monetary policy is the only effective lever of short-run stabilization. Rather The Macro Economy today strives to offer students a balanced introduction to both short and long-run macro concerns as well as an array of competing viewpoints.,.....